A Review of Environmental DNA Field and Laboratory Protocols Applied in Fish Ecology and Environmental Health - Xing, Yingchun; Gao, Wanru; Shen, Zhixin; Zhang, Yuanyuan; Bai, Jie; Cai, Xingwei; Ouyang, Jilong; Zhao, Yahui (Frontiers in Environmental Science, 2022)
Environmental DNA (eDNA) has been used in research relevant to fish ecology such as species diversity and conservation studies, threatened and invasive species monitoring, and analyses of population structure and distribution. How to choose the optimal laboratory protocols on the basis of the research targets is the first question to be considered when conducting an eDNA study. In this review, we searched 554 published articles viaEnglish and Chinese literature databases, and screened 371 articles related to eDNA research on fish ecology. The experimental methods adopted in each study were reviewed, and advantages and disad-vantages of the main protocols were analyzed. We recommend optimal protocols for regular eDNA-based fish diversity detection. Sample size is 2 L regardless of the type of water bodies; three water replicates per sampling site, and water collection sites should be designed to cover various water layers and micro-habitats within research areas. Filtration is the best method for collecting eDNA from the larger water samples; 0.45 μm glass fiber/glass microfiber (GF) filters and mixed cellulose acetate and nitrate (MCE)filters are recommended for use, and MCE filters are suitable for use in turbid waters; pre-filtration (>10 μm filtering membranes) can be used to prevent clogging. Freezing temperature storage can slow eDNA degradation, and this is the optimal way to store DNA no matter what filtering method is applied. The Qiagen DNeasy Blood and Tissue DNA extraction kit was the most economical and efficient DNA extraction method. The 12S rRNA gene is the first choice for detecting interspecies variation in fishes. The Illumina HiSeq platform can obtain sufficient data depth for fish species detection. QIIME and OBITools are inde-pendent software packages used for eDNA sequences analysis of fishes. Contamination, inhibition, lack of reference DNA data, and bioinformatic analysis are key challenges in future eDNA research, and we should develop effective experimental techniques and analysis software regarding these aspects. This review intends to help eDNA beginners to quickly understand laboratory protocols applied in fish ecological research; the information will be useful for the improvement and development of eDNA techniques in the future.